A Single-Stage Buck-Boost Three-Level Neutral-Point-Clamped Inverter with Two Input Sources for the Grid-Tied Photovoltaic Power Generation. (2nd April 2019) - Ge, Xuefeng; Chen, Mengxing; Shi, Mingming; Zhou, Qi; Li, Juan; Huang, Di; Yuan, Xiaodong; Yuan, Yubo
Abstract : This paper proposes a novel single-stage buck-boost three-Level neutral-point-clamped (NPC) inverter with two independent dc sources coupled for the grid-tied photovoltaic (PV) application, which can effectively solve the unbalanced operational conditions generally appearing between two independent PV sources. The proposed control scheme can simultaneously guarantee the maximum power point (MPP) operation of both PV sources and maintain the output waveform quality. Compared to the traditional two-stage PV inverter, the proposed NPC inverter could reduce the PV array voltage requirement and the voltage rating of dc-link capacitors; also it shows advantages in operational efficiency. MATLAB simulations and experimental results are presented to examine the performance of the proposed three-level NPC inverter.